Comparative industrial policy and cybersecurity: a framework for analysis. Issue 3 (2nd September 2018) - Aggarwal, Vinod K.; Reddie, Andrew W.
ABSTRACT: This comparative project evaluates the role of firms, governments, and other key stakeholders in the rise of industrial policy in important states in the cybersecurity industry. In particular, we focus on the US, China, Taiwan, Japan, the EU and key European states. Our goals are as follows: 1) to examine the motivation for government promotion of the cybersecurity industry; 2) to inventory existing measures employed by these countries; 3) to understand the driving forces of cybersecurity industrial policy in these countries; and 4) to examine the likely conflicts that will arise from the competitive pursuit of such industrial policies and how they might possibly be resolved through international cooperation. To this end, we provide an analytical framework to serve as the structure for this project by drawing on a variety of theoretical approaches to understand industrial policy.